Hedonizm współczesnego społeczeństwa konsumpcyjnego - Wieczorkowska, Magdalena (Annales. Etyka w Życiu Gospodarczym, 2008)
The concept of the society of consumption says that in this type of society everything is “for sale”if there is a consumer for this. That means that one can sell not only products and services but people, ideasand values as well.On the other hand, people face many global risks. Confronted by risks, they have become equalregardless of their origins, education or financial status. Anxiety about future and awareness of fragility ofa human life causes people to be more likely to indulge themselves with different pleasures. They want to“have fun before they die”.The media, advertisements and medicine offer a variety of products and services that are to makeone`s life better and to bring more pleasure and happiness to them. Contemporary hedonism is, after all,different in the sense that it does not avoid pain and suffering. People are willing to suffer in the nameof the future pleasure. Will this race to satisfy whims and desires end someday? Will the fast defeatthe carnival? Is there a place for reflection and altruism? These are some questions that this paperexamines.